KESIAPAN GURU SD DALAM MENGIMPLEMENTASIKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Dinda Agitsna, Zaskia; Sesi Susanti; Azizah Ramadhani; Khairul Fauzi; Ari Suriani; Salmaini Safitri Syam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the readiness of elementary school teachers in implementing the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum. The study employed a descriptive quantitative approach involving classroom teachers and teachers engaged in P5 implementation in several elementary schools. Data were collected through a Likert-scale questionnaire, short interviews, and documentation of project modules, teaching tools, and school activity reports. The data were analyzed using descriptive statistics in the form of mean scores, percentages, and readiness categories, while interview and documentation data were used to clarify the main findings. The results show that teacher readiness falls within the fairly ready to ready category, although it is not evenly distributed across all aspects of implementation. The strongest readiness appears in teachers’ acceptance of the policy, willingness to carry out projects, and efforts to adjust learning to students’ needs. Challenges are still found in preparing project modules, mapping the dimensions and sub-elements of the Pancasila Student Profile, conducting reflection activities, and developing assessment tools that can capture students’ learning processes more comprehensively. Factors influencing teacher readiness include conceptual understanding, training experience, principal support, teacher collaboration, and the availability of supporting facilities. These findings indicate that teacher readiness is closely related to the quality of P5 implementation in elementary schools and needs to be strengthened through continuous training, technical assistance, and a collaborative culture within the school environment.